Analysis of Turn-Taking and Gender Differences in Online EFL Classrooms - Azizeh Chalak; Mahzad Karimi (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2022)
The Covid-19 Pandemic has influenced EFL learners' turn-taking system due to the sudden shift from traditional face-to-face classes to virtual learning. This study aimed at investigating the role of gender in turn-taking patterns in online Iranian EFL classrooms. To this end, the discourse exchanges of 55 Iranian upper-intermediate online English learners were collected and analyzed. The approximate equality of male and female students paved the way to scrutinize the role of gender. The data were recorded, transcribed, and analyzed through the lens of the turn-taking system. Descriptive statistics followed by the Chi-square tests and paired comparison tests revealed that teacher selection occurred more frequently than self-selection, and using vocatives was the most preferred strategy applied by the teachers. Moreover, males took more turns compared to the female students. Therefore, gender was a determinative factor in the dominant patterns of turn-taking in online classrooms. The results could provide insightful information for teachers on creating a dialogic atmosphere in virtual classes in which all students can engage in a cooperative discussion.